2022
DOI: 10.1038/s41467-022-33530-3
|View full text |Cite
|
Sign up to set email alerts
|

A method for multiplexed full-length single-molecule sequencing of the human mitochondrial genome

Abstract: Methods to reconstruct the mitochondrial DNA (mtDNA) sequence using short-read sequencing come with an inherent bias due to amplification and mapping. They can fail to determine the phase of variants, to capture multiple deletions and to cover the mitochondrial genome evenly. Here we describe a method to target, multiplex and sequence at high coverage full-length human mitochondrial genomes as native single-molecules, utilizing the RNA-guided DNA endonuclease Cas9. Combining Cas9 induced breaks, that define th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…For this test data, sequencing reads were simulated from template genomes in which deletion events were introduced beginning at bp 5547 and extending 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 kbp with read lengths and an error profile based on our sequencing data (representative aligned reads in Supplemental Figure 1). When test data was aligned with Minimap2 and deletions called based on the CIGAR sequence of the primary alignment as previously utilized to call mtDNA deletions in nanopore data [20,27], there was a rapid decline in detection with increasing deletion size (Figure 2B). Closer examination of aligned data demonstrated that many reads containing large deletions were aligned as chimeric alignments with a “primary” alignment and a non-overlapping “Supplemental” alignment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this test data, sequencing reads were simulated from template genomes in which deletion events were introduced beginning at bp 5547 and extending 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 kbp with read lengths and an error profile based on our sequencing data (representative aligned reads in Supplemental Figure 1). When test data was aligned with Minimap2 and deletions called based on the CIGAR sequence of the primary alignment as previously utilized to call mtDNA deletions in nanopore data [20,27], there was a rapid decline in detection with increasing deletion size (Figure 2B). Closer examination of aligned data demonstrated that many reads containing large deletions were aligned as chimeric alignments with a “primary” alignment and a non-overlapping “Supplemental” alignment.…”
Section: Resultsmentioning
confidence: 99%
“…Deletions were first identified through parsing of the CIGAR sequence from the primary alignment of each read as previously reported [20,27]. We identified a total of 10,712 deletion events greater than 100 bp across all 15 samples, ranging from 101 bp to 8131 bp.…”
Section: Long-read Sequencing Of Mtdna Identifies Mtdna Deletion Brea...mentioning
confidence: 99%
“…We expect a few scattered errors in the homopolymeric regions in the mitogenomes generated herein as shown in De Vivo et al (2022) (sequencing error rates were ≥2% at the time of this study with Guppy5sup basecalling and R9.4 flow cells), but these are to be fixed as the base calling algorithms evolve or ultimately with the new sequencing kits and flow cells that increase yield and accuracy and allow for sequencing speed control (SQK‐LSK114 and flow cell R10.4) that were just released at the time of finalizing this manuscript, which were shown to reach >99% accuracy. These improvements will presumably allow single nucleotide variants and possible heteroplasmy detection (Keraite et al, 2022). On the other hand, the genomes generated in this study are likely to be more accurate than previous efforts since the methods overcomes the difficulty of sequencing the tandem repeats and long insertions, repetitions and rearrangements that can take place in vertebrate genomes (Formenti et al, 2021), provide read depth, favour long fragments of DNA and augment the proportion of the target.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of these experiments a barcoding kit or protocol for mitosequencing of multiple samples was not available and it was more practical to carry out each mitogenome sequencing in a different run to guarantee good results and reuse the flow cell up to five times. Keraite et al (2022) ran multiple samples by using different guide RNAs for each sample of human origin. However, this is less attainable with de novo sequencing of mitogenomes of fishes given their diversity but could be useful for multiple samples of the same species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation